QARAQALPAQ XALÍQ DÁSTANLARÍ MÍSALÍNDA OQÍWSHÍLARǴA ÓZ ARA BIRGE ISLESIWDI ÚYRETIWDIŃ ÁHMIYETI - Bekbagambetova, J.R. (SCIENCE and SOCIETY, 2024)
The article talks about the 4K model, which serves the result of collaborative education, that is, mutual cooperation. On the example of Karakalpak folk epics "Edige" and "Kirk kiz", examples of developing a collaborative environment and mutual cooperation among students are narrated.